Analisis Literasi Anti Korupsi dalam Pendidikan Pancasila - Zuhra Balqis Yasmilla; Istiazah Mei Canda; Ilham Hudi; Yelsa Safariani; Elsi Amanda Putri; Annisa Rahmadhani; Alga Dwi Destoarezkya (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Pancasila education has a very strategic role in shaping the character of the Indonesian nation that is free from corrupt practices. Corruption is one of the major problems that are still faced by many countries, including Indonesia. Corruption that has taken root in social, economic, and political life in Indonesia requires a comprehensive approach, one of which is through education. This study aims to analyze the role of anti-corruption literacy in Pancasila education as an effort to prevent corruption in Indonesia. This research method uses a literature review by investigating 43 journal articles published between 2020 and 2024. The results of the study show that although the application of Pancasila values in education has begun, understanding corruption and the effective implementation of Pancasila values in daily life is still a challenge. Anti-corruption literacy in Pancasila education plays a very important role in efforts to shape the character of a nation that is free from corruption. With Pancasila education equipped with anti-corruption literacy, there is great potential to form a young generation of Indonesians who are honest, have integrity, and are able to overcome corrupt practices in the future.